Pharmacogenetic Randomized Trial for Cocaine Abuse: Disulfiram and Dopamine β-Hydroxylase - Kosten, Thomas R.; Wu, Guiying; Huang, Wen; Harding, Mark J.; Hamon, Sara C.; Lappalainen, Jaakko; Nielsen, David A. (Biological psychiatry (1969), 2013)
Disulfiram has been an effective cocaine addiction pharmacotherapy, and one of its possible mechanisms of efficacy is through copper chelation and inhibition of an enzyme involved in catecholamine metabolism, dopamine β-hydroxylase (DβH), which converts dopamine to norepinephrine. A variant in the gene encoding DβH leads to reduced DβH activity, and as such, disulfiram might not be an effective treatment of cocaine dependence for individuals with this variant. This study explored that potential matching. Seventy-four cocaine- and opioid-codependent (DSM-V) subjects were stabilized on methadone for 2 weeks and subsequently randomized into disulfiram (250 mg/day, n = 34) and placebo groups (n = 40) for 10 weeks. We genotyped the DBH gene polymorphism, −1021C/T (rs1611115), that reduces DβH enzyme levels and evaluated its role for increasing cocaine free urines with disulfiram. With repeated measures analysis of variance, corrected for population structure, disulfiram pharmacotherapy reduced cocaine-positive urines from 80% to 62% (p = .0001), and this disulfiram efficacy differed by DBH genotype group. Patients with the normal DβH level genotype dropped from 84% to 56% on disulfiram (p = .0001), whereas those with the low DBH level genotype showed no disulfiram effect. This study indicates that the DBH genotype of a patient could be used to identify a subset of individuals for which disulfiram treatment might be an effective pharmacotherapy for cocaine dependence.